Optimalisasi Pusat Kesejahteraan Sosial Melalui Direktori Layanan Rujukan Berbasis Digital di Desa Rancakalong Sumedang - Wulandari, Fitri Dwi; Widiowati, Didiet (Jurnal Pengabdian Tri Bhakti, 2024)
Community Service which is integrated with the 2023 Community Practicum which will be held in Rancakalong Village, Sumedang Regency, has direction given by the PJ Regent regarding four problems which are the Main Performance Indicators (IKU) for the Sumedang Regency Region, namely reducing stunting rates, reducing extreme poverty rates, increasing village competitiveness, and improving the performance of the Social Welfare Center (Puskesos). This community service activity aims to improve the optimization of the performance of the Social Health Center. This activity involves village officials in a participatory manner as well as data mining through observation, interviews and documentation studies and outreach. The results of this activity are awareness raising of the role, duties and responsibilities of the Social Health Center as well as the establishment of a digital-based referral service directory which aims to simplify the service process, flow of information and referrals as well as data updating.